A longitudinal analysis of the progression from normal blood pressure to stage 2 hypertension: A 12-year Korean cohort - Eun Sun Yu; Kwan Hong; Byung Chul Chun (BMC, 2021)
Abstract Background The study aimed to estimate the incidence of and period of progression to stage 2 hypertension from normal blood pressure. Methods We selected a total of 21,172 normotensive individuals between 2003 and 2004 from the National Health Insurance Service-Health Screening and followed them up until 2015. The criteria for blood pressure were based on the American College of Cardiology/American Heart Association 2017 guideline (normal BP: SBP < 120 and DBP < 80 mmHg, elevated BP: SBP 120-129 and DBP < 80 mmHg, stage 1 hypertension: SBP 130-139 or DBP 80-89 mmHg, stage 2 hypertension: SBP ≥140 or DBP ≥ 90 mmHg). We classified the participants into four courses (Course A: normal BP → elevated BP → stage 1 hypertension→ stage 2 hypertension, Course B: normal BP → elevated BP → stage 2 hypertension, Course C: normal BP → stage 1 hypertension → stage 2 hypertension, Course D: normal BP → stage 2 hypertension) according to their progression from normal blood pressure to stage 2 hypertension. Results During the median 12.23 years of follow-up period, 52.8% (n= 11,168) and 23.6% (n=5004) of the participants had stage 1 and stage 2 hypertension, respectively. In particular, over 60 years old had a 2.8-fold higher incidence of stage 2 hypertension than 40-49 years old. After the follow-up period, 77.5% (n=3879) of participants with stage 2 hypertension were found to be course C (n= 2378) and D (n=1501). After the follow-up period, 77.5% (n=3879) of participants with stage 2 hypertension were found to be course C (n= 2378) and D (n=1501). The mean years of progression from normal blood pressure to stage 2 hypertension were 8.7±2.6 years (course A), 6.1±2.9 years (course B), 7.5±2.8 years (course C) and 3.2±2.0 years, respectively. Conclusions This study found that the incidence of hypertension is associated with the progression at each stage. We suggest that the strategies necessary to prevent progression to stage 2 hypertension need to be set differently for each target course.